PENERAPAN PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA (STUDI PADA DESA DI KECAMATAN TAPAKTUAN KABUPATEN ACEH SELATAN) - Amalia, Ridha; Nadirsyah, Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The purpose of this research was to determine the suitability of village financial management (planning, implementation, administrative, reporting, and accountability) in Tapaktuan sub-district according to Ministry of Home Affairs Regulation No. 113 2014 concerning Village Financial Management. This research is an descriptive model by using qualitative approach. This research using census method. The population was 16 villages in Tapaktuan sub-district. The research was conducted by interviewing the village financial management official, respondents interviewed amounted to 47 people. The result of this research showed that in general the management of village finances in Tapaktuan sub-district in the planning, implementation and accountability stages are in accordance with the Ministry of Home Affairs Regulation No. 113 2014, but there are discrepancies in the administrative and financial reporting stages of the village.